Características clínicas e implicações prognósticas do acometimento renal no mieloma múltiplo. - Martin, Luis Cuadrado [UNESP]; Niero-Melo, L.; Curi, P. R.; Soares, V. A. (My University, 1993)
The renal involvement in patients with multiple myeloma has been described as a sign of poor prognosis. The influence of renal insufficiency in the clinical patterns and in the prognosis of patients with multiple myeloma was studied retrospectively in 45 patients. Patients with renal insufficiency, at first visit, more often presented weight loss, proteinuria, hypercalcemia. The means of uricemia, ESR, were higher and the hematocritic mean was lower in patients with renal insufficiency. There was no difference in edema, arterial hypertension, fractures and bone pain. The reversibility of renal insufficiency occurred in 47% of the cases, which happened more often in the first months of the follow up. The creatinine mean was lower in patients with reversible renal insufficiency. The median survival was: patients with renal insufficiency: 11 months; patients with normal renal function: 50 months. Among patients with renal insufficiency those with recuperation of renal function showed a higher median survival (24 months) than those with irreversible renal insufficiency (1 month). The renal involvement then is frequent and often reversible. Patients with impaired renal function showed a worse prognosis; normalization of the renal function was associated with a better outcome.
Clinical characteristics and prognostic implications of renal involvement in multiple myeloma
Keywords: creatinine; acute kidney failure; adult; blood; Brazil; female; human; kidney; male; mortality; multiple myeloma; pathophysiology; prognosis; retrospective study; survival rate; Creatinine; English Abstract; Female; Human; Kidney; Kidney Failure, Acute; Male; Middle Age; Multiple Myeloma; Prognosis; Retrospective Studies; Survival Rate